Lockdown during the COVID-19 pandemic: lessons from a polarized scenario in Brazil - Camacho, Karla Gonçalves; Moore, Daniella Campelo Batalha Cox; Junqueira-Marinho, Maria de Fátima; Gomes Junior, Saint Clair; Reis, Adriana Teixeira; Abramov, Dimitri Marques (Frontiers in Psychology, 2024)
Introduction:The COVID-19 pandemic led many countries to adopt strict measures aimed at reducing circulation of the virus and mitigating the burden on health services. Among these, the lockdown was probably the most controversial and most widely debated, since it affected the population’s daily life abruptly, with consequences for people’s emotional state and the operational logic of various economic sectors. Objective:Analyze the relationship been Brazilians’ opinions on lockdown during the pandemic and individual, sociodemographic, and belief characteristics. Methods:We conducted an online survey to evaluate Brazilians’ opinions on the lockdown during the COVID-19 pandemic. We prepared a questionnaire with questions on sociodemographic aspects and individuals’ points of view towards the lockdown. We sent a link for the survey through social media and encouraged participants to also share the link in their respective social networks, as a snowball sample. Cluster Analysis is a multivariate approach that aims to segment a set of data into distinct groups, using some classification criteria. Results:From April to May 2021, the link received 33,796 free participations. We analyzed data from 33,363 participants. Pro-lockdown opinions predominated in most of the sociodemographic strata. Cluster analysis identified two groups: pro-lockdown, aligned with the scientific recommendations, and anti-lockdown, characterized by economic insecurity and denialism. Anti-lockdown participants downplayed the pandemic’s seriousness and believed in unproven measures to fight SARS-CoV-2. However, these same participants were afraid of losing their jobs and of being unable to pay their bills. Conclusions:The study identified a lack of consensus among participants concerning lockdown as a practice. Issues such as disbelief in the pandemic’s seriousness, denialism, and economic insecurity were important in the determination of the profiles identified in the study. Denialism is believed to have been a subjective defense against the economic problems resulting from social control measures and the lack of adequate social policies to deal with the pandemic. It was also highlighted that political polarization and the lack of central coordination during social distancing are crucial aspects.By analyzing Brazilians' opinions about the lockdown, considering individual characteristics, the study seeks insights to face the pandemic and prepare for future crises, contributing to more effective public health strategies.